Aplikasi Deteksi Stunting Menggunakan Algoritma Decision Tree di Puskesmas Rangkasbitung - Saputra, Meldi Anggara; Aulia, Anisa; Viktoria, Apriliani (Jurnal Ilmiah Sains dan Teknologi, 2025)
Stunting is a condition where a child experiences delayed growth, resulting in a height that is shorter than the standard for children of the same age. It is mainly caused by chronic malnutrition over a long period, especially during the first 1,000 days of life—from pregnancy to two years old. Stunting not only affects physical development but also has long-term effects on cognitive ability, immune system, and future productivity. Children who are stunted often have learning difficulties and are more prone to chronic diseases as adults. Contributing factors include maternal malnutrition, infections during pregnancy, poor dietary intake, limited access to healthcare, and lack of environmental stimulation. early intervention is essential through regular monitoring of child growth, providing balanced nutrition, improving maternal health, and educating families about proper childcare. Comprehensive and sustained efforts are needed to ensure children grow and develop optimally, reducing the risk of stunting and its long-term impacts.